Holocene climate change and past Irish societal response - Turney, C.S.M.; Baillie, Michael; Palmer, J.; Brown, David (Journal of Archaeological Science, 2006)
The extent to which North Atlantic Holocene climatic perturbations influenced past human societies is an area of considerable uncertainty and fierce debate. Ireland is ideally placed to help resolve this issue, being occupied for over 9000 yr and located on the eastern Atlantic seaboard, a region dominated by westerly airflow. Irish bog and lake tree populations provide unambiguous evidence of major shifts in surface moisture through the Holocene similar to cycles recorded in the marine realm of the North Atlantic, indicating significant changes in the latitude and intensity of zonal atmospheric circulation across the region. To test for human response to these cycles we summed the probabilities of 465 radiocarbon ages obtained from Irish archaeological contexts and observe enhanced archaeological visibility during periods of sustained wet conditions. These results suggest either increasing density of human populations in key, often defensive locations, and/or the development of subsistence strategies to overcome changing conditions, the latter recently proposed as a significant factor in avoiding societal collapse. Regardless, we demonstrate environmental change is a significantly more important factor in influencing human activity in the landscape than has hitherto been acknowledged.